Acute interstitial nephritis manifesting as a persistent nephogram - Lien Van Liedekerke, MD; Roel Beckers, MD; Kenneth Carels, MD; Laurens De Cocker, MD, PhD (Radiology Case Reports, 2023)
We report a case of a 61-year-old woman who presented to the emergency department with high inflammatory parameters and acute renal failure. Marked enlarged kidneys with persistent nephrogram were found on contrast-enhanced computed tomography . Renal biopsy showed acute interstitial nephritis. Acute interstitial nephritis must be included in the differential diagnosis in patients presenting with a persistent nephrogram.